PSYCHOLOGICAL FACTORS OF ADOLESCENT SELF-CONSCIOUSNESS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article examines how imperative feature of adults self-awareness which is related to the psychological reasons. It is universally true that the vast majority of researches that attempt to define this very case in a justified manner. For this crucial reason, author tries to indicate some significant information which is regarded as the most indespansable feature of old ones particularly in social spheres of the country successfully and perfectly.